2020
DOI: 10.1016/j.htct.2019.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Current treatment preferences in acute myeloid leukemia: a survey in Brazil

Abstract: Introduction : Most adults with acute myeloid leukemia (AML) will eventually relapse from their disease. The combination of 7-day cytarabine and an anthracycline on days 1–3 (the so called “7 + 3” regimen) can be considered standard of care of younger patients with AML. However, the treatment of the elderly ineligible for intensive chemotherapy remains a challenge. Low-dose of subcutaneous cytarabine or hypomethylating agents (HMA) have been studied this group. There are no studies investigating p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…It is possible that some physicians employ criteria intended to determine a patient's candidacy for IC to exclude them from NIC as well. According to a survey of 100 hematologists, 5% expressed a preference for using BSC only to treat patients who were either elderly or not candidates for IC (Portugal and Nucci 2019). Percival et al (2019) reported the lowest rate of NAAT (10%).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that some physicians employ criteria intended to determine a patient's candidacy for IC to exclude them from NIC as well. According to a survey of 100 hematologists, 5% expressed a preference for using BSC only to treat patients who were either elderly or not candidates for IC (Portugal and Nucci 2019). Percival et al (2019) reported the lowest rate of NAAT (10%).…”
Section: Discussionmentioning
confidence: 99%
“…There has been a survey of 2,621 hematologists in Brazil conducted between March and May of 2018. 19 The incorporation of emerging therapies for AML was highly expected in that study, with more than 60% of survey respondents having expected midostaurin and more than half doing so for GO. 19 …”
Section: Discussionmentioning
confidence: 77%
“…AML is a relatively common condition that affects predominantly older adults. 2 , 19 Once diagnosed, only one in ten older adults will live longer than 5 years. 2 , 7 Moreover, one in three elderly patients does not receive active treatment as these patients are often diagnosed with various comorbidities making them ineligible for intensive chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations